An innovative approach to teaching the Russian language to students of agricultural higher education institutions - Kasimova Muhabbat Bazarovna (Genius Journals, 2022)
This article provides information on an innovative approach to teaching the Russian language to students of agricultural higher education institutions
Keywords: creative; Improvement; innovation; competence